Black Writers, White Publishers: Marketplace Politics in Twentieth-Century African American Literature. - Dobson, Jr., Frank E. (Studies in American Naturalism)
Reviews the book "Black Writers, White Publishers: Marketplace Politics in Twentieth-Century African American Literature," by John K. Young.